Thymic Carcinoma: A Rare Cause of SVC Obstruction - Azad, Mohammad Abul Kalam; Arafat, Shohael Mahmud; Islam, Md Ariful; Islam, Md Shirajul; Quader, Monzoor; Abdullah, ABM (Bangladesh Journal of Medicine, 2013)
Superior vena caval obstruction in majority of cases is caused by bronchial carcinoma. Thymic carcinoma which by itself is a rare malignancy is a very rare cause of superior vena caval obstruction. Here by we are reporting a young ma le of 26 year of age who presented to us with feature of superior vena caval obstruction caused by thymic carcinoma. Initially he was misdiagnosed as a case of tubercular mediastinal lymhadenopathy as a cause of superior vena caval obstruction but after proper evaluation and investigation he was confirmed as a case of thymic carcinoma. Considering the rare cause of SVO and unusual age of presentation, here we are reporting a case of thymic carcinoma. DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13621 Bangladesh J Medicine 2010; 21: 105-107